2019
DOI: 10.3390/molecules24224073
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Potential of Haematococcus pluvialis Oleoresin as a Rich Source of Antioxidants

Abstract: Haematococcus pluvialis is known to be a natural source of antioxidants for numerous applications. In this study, an oleoresin rich in carotenoids extracted by supercritical CO2 treatment of H. pluvialis was extensively characterized for its antioxidant capacity. Carotenoid content, fatty acid profile, total phenol content, antioxidant capacity, and viscosity of the oleoresin were determined with the aim of ascertaining the potential of the oleoresin in terms of its antioxidant content for food applications. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 83 publications
2
11
0
1
Order By: Relevance
“…On the other hand, ARA plays a crucial role in the regulation of blood pressure and in the pathobiology of hypertension and diabetes mellitus along with the presence of potent anti-inflammatory metabolites [ 47 ]. Ruiz-Domínguez et al [ 48 ] also found EPA and ARA in similar proportions to our results (1.28% and 0.43% of total fatty acids, respectively) for extracts from H. pluvialis obtained by SFE. The results presented by Ruiz-Domínguez et al [ 48 ] demonstrated a high concentration of unsaturated fatty acids (UFA) which represents the sum of monosaturated and polyunsaturated fatty acids (MUFA+PUFA) that was approximately 78% of total fatty acid.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…On the other hand, ARA plays a crucial role in the regulation of blood pressure and in the pathobiology of hypertension and diabetes mellitus along with the presence of potent anti-inflammatory metabolites [ 47 ]. Ruiz-Domínguez et al [ 48 ] also found EPA and ARA in similar proportions to our results (1.28% and 0.43% of total fatty acids, respectively) for extracts from H. pluvialis obtained by SFE. The results presented by Ruiz-Domínguez et al [ 48 ] demonstrated a high concentration of unsaturated fatty acids (UFA) which represents the sum of monosaturated and polyunsaturated fatty acids (MUFA+PUFA) that was approximately 78% of total fatty acid.…”
Section: Resultssupporting
confidence: 92%
“…Ruiz-Domínguez et al [ 48 ] also found EPA and ARA in similar proportions to our results (1.28% and 0.43% of total fatty acids, respectively) for extracts from H. pluvialis obtained by SFE. The results presented by Ruiz-Domínguez et al [ 48 ] demonstrated a high concentration of unsaturated fatty acids (UFA) which represents the sum of monosaturated and polyunsaturated fatty acids (MUFA+PUFA) that was approximately 78% of total fatty acid. The present study also showed relevant content of UFA in the range from 78 to 79% of total fatty acids without significant differences (equivalent to 381–448 mg/g extract).…”
Section: Resultssupporting
confidence: 92%
“…5 In this context, the search for other compounds of interest that enable a greater use of biomass has been increased, in turn enriching the bioactive power of astaxanthin-rich biomass in a synergic way. 6 In contrast to the 5% astaxanthin content that H. pluvialis can store, the lipid content can reach approximately 35% of dry weight, with a high amount of fatty acids of the omega-3 and omega-6 series. 7,8 In contrast, the potential content of H. pluvialis as a source of fatty acids has generated great interest in recent years, having a signicant impact on the nutraceutical sector.…”
Section: Introductionmentioning
confidence: 99%
“…Under certain stress conditions, the H. pluvialis has been shown to accumulate up to 3-5% DW of astaxanthin [4]. Furthermore, in carotenoids oleoresin extracted from H. pluvialis by supercritical CO 2 treatment is high [16]. The antioxidant content of the oleoresin is important for food applications.…”
Section: Carotenoidmentioning
confidence: 99%